PROFITABILITY OF FAMILY FARMS DIRECTED AT CROP PRODUCTION - Munćan, Petar; Todorović, Saša; Munćan, Mihajlo (Economics of Agriculture, 2014)
The effciency in crop production depends on, on the one hand, achieved yields and selling prices (production value) and, on the other hand, on the incurred production costs. These data suggest different economic indicators which indicate the effciency of farm operations. Data on the basic parameters of production were collected using the method of survey, which was conducted during the fve-year period (2009-2013) on the selected 40 family farms (<100 ha), divided into fve groups, each consisting of 8 farms, oriented exclusively towards crop production in the region of two municipalities in the South Banat District. Production effciency and rational usage of available resources of observed family farms were measured by calculating their proft including state incentives for agriculture and evaluating their own resources engaged in the production.